Africa’s litigated democracy - Baulch, Bob; Resnick, Danielle (2020)
The fact that African opposition parties increasingly turn to the courts when they lose elections indicates that perceptions of judicial independence are improving. But frequent recourse to the courts can undermine trust in the electoral process and indicates that basic democratic mechanisms are not functioning properly.